Perfil biosicosexual y social de la persona ostomizada que acuden a medicáncer, Medellín 1995 (1997)
ABSTRACT: The result of a research on “the byo-psico-social profile of ostomised patients”, who were selected from the Medicancer rehabilitation program and were diagnosed with definitive ostomy are presented in this article. The pre and post surgery preparation received by the patients; the way how ostomy is handled; the major emotional reactions; the components of the self-framework: the self concept, the self-performance, and the self-respect that influence on their behaviour are described. Furthermore, the sexual manifestations are identified as well as the features, vital cycle, functions, and relationships of the patients’ family. Finally, the conclusions of this study and the recommendations according tho the medical care levels are also stated.